Mäzenatentum, Naturwissenschaft und Politik im Habsburgerreich und in der Ersten Republik Österreich - Reiter, Wolfgang L. (Österreichische Zeitschrift für Geschichtswissenschaften, 2014)
This paper analyzes the patronage of the sciences by Vienna’s liberal bourgeoisie in the days of the late Habsburg monarchy, a period of public and private advancements in all sciences. It specifically focuses on the establishment of scientifically highly successful prizes and institutions within the Vienna Academy of the Sciences. Regarding the research of radioactivity in particular, patronage by founding a new research institution (Institut für Radiumforschung at the Academy) triggered and incited internationally competitive research. All this came to an end in 1938.